Insights of hepatozoonosis transmitted by H. Canis - Henrique, Anna Luisa Pizzaia; Miranda, Lívia Mendes; Castilioni, Leonardo (Revista de Ciências Agroveterinárias, 2024)
Hepatozoonosis caused by H. Canis is a hemoparasitic disease transmitted by the tick Rhipicephalus sanguineus. In vertebrate hosts, the disease primarily occurs through ingestion of the hemoparasite or its components. Hepatozoon spp. infection typically remains subclinical, only becoming diagnosed upon microscopic observation of the hemoparasite during blood smear analysis. However, in certain instances, moderate or severe clinical manifestations may occur. Due to limited research focusing on Hepatozoonosis, diagnosis can present challenges, as well as selecting the appropriate test to confirm it, with PCR being considered the preferred method for detection. A two-and-a-half-month-old Golden Retriever puppy was examined, exhibiting symptoms of vomiting, lethargy, bloody diarrhea, anorexia, and hyperthermia (39°C - 102,2°F). Diagnosis was confirmed by observation of Hepatozoon spp. parasites in the blood smear, alongside severe anemia, presence of microagglutination, and elevated total protein levels. The treatment was initiated with Doxycycline, and following the patient´s improvement, the owner opted to proceed with castration and subsequently administer two doses of Imidocarb Dipropionate at 5mg/kg with a 14-day interval.